The Reform of Public Procurement Sector in Bulgaria – A New Beginning, New Possibilities - Pavlova, Miglena (Research Papers, 2016)
With the adopted by the European Union in 2014 Directives on awarding of public procurement by the so called “classical” and “sectoral” contracting authorities, it was implemented a reform of the community legislation in this field, aiming modernization and simplification of the rules and overall optimization of the awarding process. For Bulgaria, as a Member-State, this caused a number of new engagements, including the necessity of adoption of an entirely new frame Public Procurement Law and of secondary legislation acts, connected with its implementation, as well as gradually introduction of e-procurement.At the same time, in accordance with the assigned objectives in the adopted by the Government strategic documents for the development of this sector in the next few years, on national level other substantial measures took place, including: changes in the existing institutional system, aimed at strengthening of the administrative capacity and optimizing of the work of the state authorities and institutions with powers in the field of methodology, re-viewing and control of public procurement; planning and conducting of trainings for different targeted groups (and mostly the contracting authorities); developing of guidances, methodological guidelines and indications in connection with identified problems during implementation of the legislation in the public procurement field, as well as preparation of the process for development and publishing of standardized requirements and documents, connected with most frequently awarded public procurements; strengthening of the centralized public procurement awarding in the country etc.Because of the fact that through the Public Procurement Law is regulated the movement of substantial part of the public finances, and also of funds, connected with the implementation of specific activities in the field of energy, water supply and transportation, the introduction of the new legislation has a determining importance for the whole economic environment in the country. Given the cumulative amount of the spent in this way funds, the public procurements influence the behaviour of individual economic subjects, as well as the development of whole economic sectors, and the implementation of policies, connected with achieving different social, industrial and ecological aims in their awarding, could assist also the ensuring of sustainable development. This defines the exceptional public importance of the issues, concerning the changes in the legal regulation of the relations that arise and are implemented within the procurement process.
Keywords: Public procurement law; E-procurement; Public resources